Corporate Governance Role in Improving the Financial Information Quality within the Saudi Electricity Company - Baabbad, Arwa Hassan (Journal of Economic, Administrative and Legal Sciences, 2020)
The present study aimed to find out the role of corporate governance in improving the quality of information in the Saudi Electricity Company. The researcher used the descriptive survey methodology. As to achieve the study objectives، the researcher utilized the questionnaire tool، in which the study sample (50) members of SEC distributed into employees، managers and decision makers. The study concluded to many results، among of which are: there is a statistically significant relationship between the availability of corporate governance system and performance improvement of the Saudi Electricity Company، there is a statistically significant relationship between corporate governance and appropriateness in improving the performance of the Saudi Electricity Company، it was also found that there is a statistically significant relationship between corporate governance and optimal disclosure in improving the performance of Saudi Electricity Company. The study also found that there is a statistically significant relationship between corporate governance and the right timing in improving the performance of the Saudi Electricity Company. The study suggested number of recommendations، among of which are: the importance of the shareholding companies to comply with the corporate governance regulations considering the interest of companies and their shareholders and all other parties benefiting from the financial statements، attempting to take advantage of the multiple benefits of corporate governance and expand its application in the various economic units in Saudi Arabia، conduct studies on companies that applies the requirement of the Corporate Governance Regulations، and the impact of the application of corporate governance on the shares of these units to find out the relationship between the quality of accounting information in light of the application of corporate governance and the stock market from another angle، imposing deterrent penalties concerning the Corporate Governance Regulations on companies that did not apply this regulation.